Maryam: The Blessed Virgin of Islam - Sarbini, Peter Bruno (Perspektif, 2013)
The article argues that Maryam has a special and important position in the Holy Quran and hadith or tradition. As a holy and gentle and pious woman, she was chosen in a special way by Allah to bear and give birth to Isa a.s. Although Maryam is not recognized and accepted as the mother of God, but she is respected indeed. She is even asked for help through her prayers. She is also regarded as a holy woman who defended her dignity and obeyed Allah, and she trusted His Word and Commandments. She is always closed to God and truly blessed as a holy woman. Therefore Maryam is really the blessed virgin of Islam.